To the mean-field theory of a two-sublattice antiferromagnet - Zvyagin, A.A.; Skorobagat`ko, G.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Numerical solutions of the mean-field theory of a two-sublattice antiferromagnet with a strongcrystalline electric field are studied. The validity of the solutions was checked with the help of known analytical results for the special case of the lowest doublet (S = 1/2). For larger values of the lowest multiplet (S > 1/2). the temperature and magnetic field dependencies of the antiferromagnetic order parameter and the total magnetization are calculated and their features are analyzed. We predict new re-entrant phase transitions between Néel and paramagnetic phases for S ≥ 1.